Pengemasan Pesan Pelestarian Kain Tradisional Indonesia di Media Sosial Instagram @Pemudaberkain - Nabilah Puspita Ardhani; Augustin Mustika Chairil (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
Social media, such as Instagram, has become an essential tool in raising awareness of social issues such as cultural preservation. The @pemudaberkain account is an initiative move that utilizes Instagram to reintroduce traditional Indonesian fabric into everyday life. The goal and focus of the @pemudaberkain account is to attract the interest of the younger generation in appreciating and using traditional Indonesian fabric. This study employs a qualitative content analysis method to examine how the preservation message is conveyed on the @pemudaberkain account during the period from November 2023 to July 2024. The findings show that @pemudaberkain utilizes various forms of content, including informative and persuasive messaging, to influence behavior change, encouraging audiences to adopt traditional fabrics both in formal occasions and casual styles. The @pemudaberkain account also collaborates with influence and external parties to expand its audience reach. Using the social marketing approach by Philip Kotler, @pemudaberkain aims to spread the idea of cultural preservation. Furthermore, @pemudaberkain has effectively used Instagram as a medium of cultural preservation, as evidenced by the positive audience responses, such as praise-filled comments, and audience’s behavior shift toward wearing traditional Indonesian fabrics as part of their everyday attire.